Abisso e verticalità in William Hope Hodgson - Dall'Igna, Antonio (Filosofia, 2016)
The present essay examines William Hope Hodgson’s narrative produc- tion in connection with Giordano Bruno and Georges Bataille. His work prob- lematizes the concept of abyss – the locus of the undifferentiated and chaos – and the ensuing forces, which manifest both in the cosmos and, constantly, in human existence. What is more, William Hope Hodgson’s writing raises a reflection on nature and the functions of ‘vertical forms’, namely those constructions and arti- fices – among which is human form itself – which humankind employs to sound out, restrain, and translate the dark side of reality, which exists at once within and without the world and its inhabitants. As far as the explorations of the abyss and chaos are concerned, special attention is conferred to the difference between the The Night Land and the other novels written by Hope Hodgson.